Achievements and difficulties in ruminant livestock Development in the humid and subhumid zones of West and Central Africa - Kaufmann, Ralph R. von; Peters, Kurt J. (University of Utrecht, 1990)
Looks into achievements and difficulties in ruminant livestock Development in the humid and subhumid zones of West and Central Africa. Discusses the ecological and economic circumstances and the changing environment. Gives brief descriptions of the achievments including disease control, tsetse control, smallholder fattening, sheep production and marketing and the difficulties including disease, social and institutional constraints.